2016
DOI: 10.1111/mec.13507
|View full text |Cite
|
Sign up to set email alerts
|

Responses to simulated winter conditions differ between threespine stickleback ecotypes

Abstract: Abiotic factors can act as barriers to colonization and drive local adaptation. During colonization, organisms may cope with changes in abiotic factors using existing phenotypic plasticity, but the role of phenotypic plasticity in assisting or hindering the process of local adaptation remains unclear. To address these questions, we explore the role of winter conditions in driving divergence during freshwater colonization and the effects of plasticity on local adaptation in ancestral marine and derived freshwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 83 publications
(184 reference statements)
3
28
0
Order By: Relevance
“…This pattern is consistent with our previous study that showed that the freshwater ecotype maintains higher ECaC expression at low salinity than the marine ecotype (Gibbons et al . ), and suggests the evolution of enhanced plasticity in the freshwater ecotype, potentially resulting in improved uptake of this ion, resulting in a pattern of cogradient variation in the expression of this gene. Similarly for NKA, qRT–PCR detected a significant difference in gill gene expression between the two ecotypes, which was not detected in the RNA‐seq data, with the freshwater ecotype having slightly higher expression at each acclimation salinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern is consistent with our previous study that showed that the freshwater ecotype maintains higher ECaC expression at low salinity than the marine ecotype (Gibbons et al . ), and suggests the evolution of enhanced plasticity in the freshwater ecotype, potentially resulting in improved uptake of this ion, resulting in a pattern of cogradient variation in the expression of this gene. Similarly for NKA, qRT–PCR detected a significant difference in gill gene expression between the two ecotypes, which was not detected in the RNA‐seq data, with the freshwater ecotype having slightly higher expression at each acclimation salinity.…”
Section: Discussionmentioning
confidence: 99%
“…Primer sequences were as in Gibbons et al . () and are reported here in Table (Supporting information). qRT–PCR was performed essentially as in Gibbons et al .…”
Section: Methodsmentioning
confidence: 99%
“…Marine and freshwater stickleback crosses have high viability in either salinity (Marchinko & Schluter ; Gibbons et al . ). Tanks were kept at 18 °C on a seasonally variable photoperiod, were held at similar densities, and allowed to grow for c .…”
Section: Methodsmentioning
confidence: 97%
“…; Gibbons et al . ). In situ evolution may be particularly important for organisms that cannot track their optimal climate conditions through space due to limited inherent dispersal abilities or extensive distances between habitat patches (Aitken et al .…”
Section: Introductionmentioning
confidence: 97%
“…Substantial evidence indicates that these responses are often mediated by genetic and physiological constraints that exist within populations (Etterson & Shaw 2001;Norberg et al 2012;Anderson 2016), underscoring the importance of evolutionary history in shaping species' responses to ongoing and future environmental change. Most recently, scientists have been evaluating the extent to which ongoing and future evolutionary change, such as rapid adaptation, can facilitate persistence in the face of global warming (Franks et al 2007;Anderson et al 2012;Gibbons et al 2016). In situ evolution may be particularly important for organisms that cannot track their optimal climate conditions through space due to limited inherent dispersal abilities or extensive distances between habitat patches (Aitken et al 2008;Angert et al 2011;Schloss et al 2012).…”
Section: Introductionmentioning
confidence: 99%